Towards tailored regimens in the treatment of drug-resistant tuberculosis: a retrospective study in two Italian reference Centres - Riccardi, Niccolò; Alagna, Riccardo; Saderi, Laura; Ferrarese, Maurizio; Castellotti, Paola; Mazzola, Ester; De Lorenzo, Saverio; Viggiani, Pietro; Udwadia, Zarir; Besozzi, Giorgio; Cirillo, Daniela; Sotgiu, Giovanni; et al. (BMC infectious diseases, 2019)
Background The increased incidence of drug-resistant TB is a major challenge for effective TB control. Limited therapeutic options and poor treatment outcomes of DR-TB may increase drug-resistance rates. The objective of the study is to retrospectively compare MDR-TB and pre-XDR-TB treatment regimens and outcomes in two large TB reference centres in Italy from January 2000 to January 2015. Methods A retrospective, multicentre study was conducted at the Regional TB Reference Centre Villa Marelli Institute (Milan) and at the Reference Center for MDR-TB and HIV-TB, Eugenio Morelli Hospital (Sondalo). The supra-national Reference Laboratory in Milan performed DST. Inclusion criteria were: age ≥ 18 and culture-confirmed diagnosis of MDR- or pre-XDR TB. Chi-square or Fisher exact test was used to detect differences in the comparison between treatment outcomes, therapeutic regimens, and drug-resistances. Computations were performed with STATA 15. Results A total of 134 patients were selected. Median (IQR) age at admission was 33 (26–41) years and 90 patients (67.2%) were male. Pulmonary TB was diagnosed in 124 (92.5%) patients. MDR- and pre-XDR-TB cases were 91 (67.9%) and 43 (32.1%), respectively. The WHO shorter MDR-TB regimen could have been prescribed in 16/84 (19.1%) patients. Treatment success was not statistically different between MDR- and pre-XDR-TB (81.3% VS. 81.4%; P = 0.99). Mortality in MDR-TB and pre-XDR-TB groups was 4.4 and 9.3%, respectively ( P = 0.2). Median duration of treatment was 18 months and a total of 110 different regimens were administered. Exposure to linezolid, meropenem, and amikacin was associated with a better outcome in both groups ( P = 0.001, P < 0.001, and P = 0.004, respectively). Conclusions Tailored treatment regimens based on DST results can achieve successful outcomes in patients with pre-XDR-TB.